PENGARUH ARAH SERAT DAN SUSUNAN LAPISAN TERHADAP FAKTOR KONSENTRASI TEGANGAN PADA KOMPOSIT LAMINATE CARBONIEPOXY AS4/3501-6 BERLUBAN G LIN GKARAN DAN ELLIPS - Puja, IGN Wiratmaja; B, Satryo Soemantri; Riyanto, Budi (Mesin, 1998)
In recent years, ï¬ber-matrix composite laminates have been widely used in mechanical structures. Due to functional design requirements, the laminates may contain holes that could cause stress concentration. Unlike isotropic plate, where the stress concentration depend upon geometric parameter and loading conditions, stress concentration factor of ï¬ber-matrix composite is also depend on the anisotropic properties such as ï¬ber direction and angle ply. This paper present intensive studies of the inï¬uence of the ï¬ber direction and angle ply to the stress concentration factors for composite laminate containing circular and elliptical hole under uniaxial loading. The stress concentration factor curves are presented for various angle ply, ï¬ber direction, and geometric parameter. These curves could be used by designer to obtain the optimum design of laminate structure containing hole.